Pengaruh Beberapa Jenis Ekstrak Tanaman sebagai Moluskisida Nabati terhadap Keong Mas (Pomacea canaliculata) - Agus Kardinan; Momo Iskandar (Jurnal Perlindungan Tanaman Indonesia, 1997)
Research has been carried out at the Pest and Disease Laboratory, Research Institute for Spices and Medicinal Crops, Bogar, in the 1997. Research consisted of three parts, those were; (I) The toxicity of Dens elliptica, Blumea balsamifera, and methaldehyde, by determining the LC50 values, (2) Effect of the leaves of B.balsamifera, Euphorbia tirucalli and Tephrosia vogelii, (3) Effect of the most poisonous plant as ovicides. Result showed that D.elliptica was the most poisonous material to golden snail with its LC50 value was 400ppm, but it was still under the toxicity value of methaldehyde (11. 78 ppm). There was no significant difference among B.balsamifera, T.vogelii and E. canaliculata, but extract of B.balsarnifera tended to be better material among those plant extracts tested. The extract of D.elliptica did not affect egg hatching of golden snail.